An Appraisal of The Legality of Translating Jumu’ah Khutbah in Nigeria - Mustapha, Abdur-Razzaq Solagberu Balogun Mustapha Balogun (al-'adalah, 2022)
Khutbah is one the stipulated condition that distinguish Jumucah prayer from other obligatory five ritual daily prayers.  By the time Islam spread to what is now known as Nigeria, the Khutbah used to be rendered in Arabic without any attempt to translate it to any local language.  However, with passage of time the population of Muslims continues to increase.  As a result of that, there are agitations and counter-agitation on the need to either translate the khutbah into a local languages or to render it in a vernacular.  The issue of legality comes in as a means of justifying either of the duo agitations.  The objective of this research paper is to examine the legality or otherwise of translating the khutbah especially in a country like Nigeria where a section of the Muslims who observe their Jumu’ah prayer could not comprehend the language in which the khutbah is being delivered. The method adopted in the research is based on both participatory and non-participatory observations.  The end-result of the research reveals that the khutbah can be legally translated considering a large population of the worshippers who could not comprehend the language of communication i.e. Arabic. By extention, the khutbah of religious festivals such as cIdul-Fitr and cIdul-Adha be translated too.  Similarly ceremonial events where Khutbah is rendered in Arabic should also be translated.  All these will afford the larger number of the congregation not only to be exposed to the stand and teachings of Islam on current issues but will also enable them to appreciate the teachings of Islam.